Magnetic Fe3O4@SiO2/Pd and Fe3O4@SiO2/Pd‐M (M=Ag, Cu and Zn) Catalysts for Selective Hydrogenation of Phenylacetylene. Issue 18 (7th November 2016) - Yang, Lei; Chen, Xiangling; Zhou, Zhiming; Zhang, Rui; Li, Li; Cheng, Zhenmin; Fang, Xiangchen
Abstract: Magnetic core‐shell monometallic Fe3 O4 @SiO2 /Pd and bimetallic Fe3 O4 @SiO2 /Pd−M (M=Ag, Cu and Zn) catalysts with low Pd loading were prepared using a modified Stöber method followed by an ion‐exchange technique, and applied to the selective hydrogenation of phenylacetylene. The structure and magnetism of the catalysts were investigated using N2 physisorption, XRD, FT‐IR, ICP‐OES, H2 ‐TPR, CO chemisorption, DRIFTS, HRTEM and vibrating sample magnetometer. The characterization results showed that the magnetic catalyst had smaller Pd particle size than the non‐magnetic catalyst; the thinner the silica shell of the magnetic catalyst, the stronger the magnetic intensity and hence the smaller the Pd particle size; the PdM alloy was formed for bimetallic catalysts and geometric and electronic effects occur. By comparing the activity and selectivity of different catalysts, it was found that the catalyst with smaller Pd particle size generally exhibited a higher apparent activity and selectivity to styrene but a lower specific activity, demonstrating the structure‐sensitive catalytic activity for selective hydrogenation of phenylacetylene on the magnetic Pd supported catalysts. In addition, all the bimetallic catalysts displayed higher selectivity but lower activity than the monometallic catalysts as a result of the presence of the PdM alloy. In particular, a Fe3 O4 @SiO2 /Pd−Zn catalyst with the shell thickness of about 80 nm and the Pd and Zn loadings of 0.31 and 1.79 wt%, respectively, showed the best selectivity to styrene, being 86.1 % at above 99.5 % conversion of phenylacetylene. Furthermore, this catalyst maintained its activity and selectivity even after being reused ten times. Abstract : Magnetic Fe3 O4 @SiO2 /Pd and Fe3 O4 @SiO2 /Pd−M (M=Ag, Cu and Zn) core‐shell catalysts are prepared by combining a modified Stöber method and an ion‐exchange technique. The Pd particle size can be tailored by controlling the thickness of the silica shell: the thinner the shell, the smaller the Pd particle size is. Fe3 O4 @SiO2 /Pd−Zn with a shell thickness of about 80 nm exhibits the best activity, selectivity to styrene and cyclic stability (10 cycles) in the selective hydrogenation of phenylacetylene.